Bond of recycled coarse aggregate concrete: Model uncertainty and reliability-based calibration of design equations. (15th July 2021) - Pacheco, João Nuno; de Brito, Jorge; Chastre, Carlos; Evangelista, Luís
Highlights: Influence of recycled aggregates on the model uncertainty of Eurocode bond strength. Recycled aggregates increase scatter and decrease bias of the model uncertainty. Similar relative effect of recycled aggregate on pullout and lap splice bond strength. Stochastic modelling of bond strength uncertainty for recycled aggregate concrete. Calibration of partial factor for bond length design for recycled aggregate concrete. Abstract: This paper concerns the design of lap splice lengths for ribbed steel reinforcement bars embedded in concrete produced with coarse recycled concrete aggregates. Recycled aggregates are weaker and typically lead to concrete with lower tensile strength. Both aspects change the model uncertainty of bond strength formulae and a major topic of the paper is the influence of recycled aggregates on the model uncertainty of the bond strength model of fib Bulletin 72. A stochastic model for this model uncertainty is developed from a meta-analysis. The model uncertainty, estimated from analogue specimens made with either natural aggregate concrete or recycled aggregate concrete, is compared and the incorporation of recycled aggregates was indeed found to have a detrimental influence on the model uncertainty. A partial factor for lap splice length design is calibrated through reliability analyses so that the probability of failure of the bond length design of recycled aggregate concrete is equivalent to that of natural aggregate concrete. Two design equations were studied: that of the fib Bulletin 72 and that of the D6 draft of the second generation of Eurocode 2.